4³ ⁻ ˣ . (1/8)²ˣ ⁺ ⁵ = 16ˣ ⁺ ³
4 = 2², 8 = 2³, 16 = 2⁴
(2²)³ ⁻ ˣ . (1/2³)²ˣ ⁺ ⁵ = (2⁴)ˣ ⁺ ³
(2²)³ ⁻ ˣ . (2⁻³)²ˣ ⁺ ⁵ = (2⁴)ˣ ⁺ ³
Multiply out the powers.
2²⁽³ ⁻ ˣ⁾. 2⁻³⁽²ˣ ⁺ ⁵⁾ = 2⁴⁽ˣ ⁺ ³⁾
2*(3 - x) = 2*3 - 2*x = 6 - 2x
-3*(2x +5) = -3*2x - 3*5 = -6x - 15
4(x +3) = 4*x + 4*3 = 4x + 12
2²⁽³ ⁻ ˣ⁾. 2⁻³⁽²ˣ ⁺ ⁵⁾ = 2⁴⁽ˣ ⁺ ³⁾
2⁶ ⁻ ²ˣ . 2⁻⁶ˣ ⁻ ¹⁵ = 2⁴ˣ ⁺ ¹²
On the left hand side we add the powers, because it is a multiplication process.
2⁶ ⁻ ²ˣ ⁺ ⁽⁻⁶ˣ ⁻ ¹⁵⁾ = 2⁴ˣ ⁺ ¹²
Since the bases of the equation are the same, hence the powers are the same.
6 - 2x + (-6x -15) = 4x +12
6 - 2x - 6x - 15 = 4x + 12
-2x - 6x - 4x = 12 - 6 + 15
-12x = 21
Divide by -12.
x =21/-12, cancel through by 3.
x = -7/4
I hope this helped.